Preparation and characterization of Poly (lactic acid) (PLA)/Polyamide 6 (PA6)/ Graphene Nanoplatelet (GNP) blends bio-based nanocomposites - Mat Piah, Mohd Bijarimi; Mohd Yusof, Mohammad Amirul; Ahmad, Mohammad Norazmi; Ramli, Azizan; Mat Desa, Mohd Shaiful Zaidi; Desa, Md Anuar; Abu Samah, Mohd Armi (Institute of Physics Publishing, 2019)
Biodegradable PLA is commonly derived from renewable resources and benign to the environment.It is a brittle thermoplastic with high strength and modulus; thus a suitable candidate for replacing conventional petroleum-based plastic.However,due to its limitation, PLA needs to be blended with other polymers and ﬁllersforpropertiesmodiﬁcations.The aim of this work was to prepare PLA/ PA6/GNP nano composites and characterize on the mechanical,thermal,chemical and dispersion of nanoﬁller in binary blend systems. PLA/PA6/GNP nano composites were blended by using a Haake twin screw extruder via melt intercalation method. The ratio of the polymer matrix was ﬁxed at 20:80 and the processing temperature was in the range of 205°C to 260°C. Graphene nano platelet ﬁllers were then loaded in the PLA/PA6 blends with 0.5,1.0,3.0 and 5.0 wt%. It was found that PLA/PA6/ GNP(5.0) nano composites were the overall highest in terms of thermal and mechanical properties. PLA/PA6/GNP nano composites improved the mechanical properties in terms of elongation at break and maximum stress as well as improved the degradation temperature. The property improvement in the nano composites was due to the dispersion of GNP in the polymer matrix. It was also found that there was no chemical interaction between a functional group of nano composites. It can be concluded that nano composites were incompatible and immiscible with PA6.